Defect engineering for shallow n‐type junctions in germanium: Facts and fiction. Issue 11 (18th July 2016) - Simoen, Eddy; Schaekers, Marc; Liu, Jinbiao; Luo, Jun; Zhao, Chao; Barla, Kathy; Collaert, Nadine
Abstract : An overview is given on the status of n‐type dopant activation and diffusion in Ge, based on a standard ion implantation and annealing scheme. Emphasis is on defect engineering approaches to optimize either or both parameters. A detailed discussion is given on the use of co‐implantation by neutral or other n‐type dopants. As a case study, the impact of the C ion implantation energy and dose on n‐type junctions in p‐Ge by P + C co‐implantation will be given. It is demonstrated that for fixed P implant conditions, there exist an optimum energy and dose for achieving a minimum junction depth by the formation of C–PV complexes. An alternative approach is the use of self‐interstitial management at the end‐of‐range of the P implantation. Finally, an overview is given of alternatives for obtaining shallow, highly activated n‐type junctions in Ge. They rely on: non‐standard implantation schemes, ultra‐short annealing methods or relying on in situ doped epitaxial deposition. Abstract : In case you want to find out the latest in n‐type doping in Ge and what co‐implantation or end‐of‐range damage management can do for you, please have a look at this review. In addition, alternative doping and activation annealing strategies are highlighted.